The significance of delivery methods and fetal gender in reducing stillbirth rate: Using the generalized regression model - Nozad H. Mahmood; Dler H. Kadir; Rebaz O. Yahya; Hawkar Q. Birdawod (Elsevier, 2024)
Aim: Despite stillbirth being a significant burden for maternal lives, families, and communities worldwide, it is often neglected and overlooked in many countries. The fetal gender and the delivery method are two interaction factors that directly impact the stillbirth rate. This study aimed to identify the impact of fetal gender on stillbirth delivery methods, either cesarean section or vaginal delivery. Method: The current research analyzed the stillbirths recorded over ten years between January 1st, 2008, and December 31st, 2017, obtained from the Maternity Teaching Hospital in Erbil City, the capital of the Kurdistan Region of Iraq. Results: The results showed that stillbirths remain a significant public health concern in the region, with 11.7 stillbirths occurring for every 1000 deliveries. The generalized regression model for each normal, beta, and gamma distribution was used to determine the best fit of the data. The study found that for fetal males, vaginal delivery reduced the stillbirth rate by 4.2 % and the cesarean section rate by 3.6 % while for fetal females, vaginal delivery reduced the stillbirth rate by 4.7 % and the cesarean section rate by 6 %. Conclusion: The findings suggest that healthcare in the region should prioritize reducing the incidence of stillbirths during pregnancy and delivery, considering factors such as fetal gender and delivery mode.